2019
DOI: 10.1007/s12328-019-01037-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship(s) between obesity and inflammatory bowel diseases: possible intertwined pathogenic mechanisms

Abstract: The inflammatory bowel diseases, Crohn's and ulcerative colitis have increased in incidence and prevalence from the mideighteen to the late nineteen centuries. From then to the current twenty-first century there has been a more rapid expansion of these disease to areas previously experiencing low rates. This latter expansion coincides with the current obesity pandemic which also began toward the end of the last century. Although the two diseases have radically different frequencies, there are interesting links… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 141 publications
(230 reference statements)
1
39
0
1
Order By: Relevance
“…Moreover, obesity has been shown to have an adverse effect on biological therapy. The literature mainly presents such connections for infliximab and adalimumab [ 56 ]. Due to increased body weight, there is a faster optimization of the patients’ infliximab levels and therefore a higher dose regimen may be necessary [ 57 ].…”
Section: Influence Of Obesity On the Course Of Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, obesity has been shown to have an adverse effect on biological therapy. The literature mainly presents such connections for infliximab and adalimumab [ 56 ]. Due to increased body weight, there is a faster optimization of the patients’ infliximab levels and therefore a higher dose regimen may be necessary [ 57 ].…”
Section: Influence Of Obesity On the Course Of Ibdmentioning
confidence: 99%
“…In addition, bacterial lipopolysaccharide (LPS) may trigger a signal to induce low-grade inflammation that contributes to diabetes, obesity and the metabolic syndrome [ 83 ]. In both IBD and obesity, there is an increase in Proteobacteria, Ruminococcus gnavus and a decrease in Clostridium (leptum) and Faecalibacterium prausnitzii [ 56 ].…”
Section: Intestinal Microbiota Excess Body Weight and Ibdmentioning
confidence: 99%
“…Recent epidemiological studies have also shown that incidence of IBD is rising in parallel with obesity prevalence [ 4 , 5 ]. Moreover, the rate of hospitalization and surgery are more frequent among IBD patients with obesity [ 6 ]. Scientific studies have suggested that, genetics, gut microbiome, and the immune system may play critical roles in IBD, however, this has not completely understood yet [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent epidemiological studies have also shown that increasing rate of IBD is parallel with the obesity prevalence [4,5]. Moreover, hospitalization and surgery are more frequent among IBD patients with obesity [6]. Although it is not fully understood yet, scienti c studies have suggested that, genetics, gut microbiome, and the immune system may play critical roles in IBD [7].…”
Section: Introductionmentioning
confidence: 99%